Money Minute: Using short informational videos during COVID-19 - Christopher T. Sneed; Ann A. Berry; Shelly N. Barnes; Donna D. Calhoun; Tracy V. Hagan; Marci H. Hethmon; Karen D. Jones; Barbara Metzger ([TEST] Journal of Extension, 2021)
The COVID-19 pandemic has created a money crunch for some families. To help families struggling financially while capitalizing on at-home time, The University of Tennessee (UT) Extension consumer economics leadership team developed a series of money management videos called Money Minute. The primary purpose of the videos was to provide research-based financial education during this time of financial hardships. Filmed using Zoom, each video offers a piece of research-based information, additional resources, and a call to action. The video series proved to be effective in reaching clientele with financial information in the midst of a pandemic.
Keywords: COVID-19; Zoom; Social Media; distance technology; money